Telecom Management in Emerging Economies Evolutionary and Contemporary Perspectives - Medudula, Murali Krishna; Sagar, Mahim; Gandhi, Ravi Parkash (Springer India : Imprint: Springer, 2016)
This book discusses the ideas, interventions (by different players) and technological revolutions that have transformed the telecom industry to propel it towards a growth cycle. Pursuing a comprehensive approach, it examines highly topical issues in depth, e.g. mobile data security via 4G, the new industrial revolution, green telecommunications, and consumer awareness of radio signals. Along with input from regulators, government organizations and industry players, expert opinion columns in each chapter clearly present the viewpoints of the industry and ministry. Several graphical tools are used throughout the book, helping readers to contemplate the text in different ways and to make concepts more "hands-on." Readers will also gain a holistic perspective of the industry (key players, regulatory bodies and the consumer) and a clearer understanding of various policy issues and their implementation mechanisms, business dynamics and technology issues in this sector.